Decoding TDP-43: the molecular chameleon of neurodegenerative diseases - Jixiang Zeng; Chunmei Luo; Yang Jiang; Tao Hu; Bixia Lin; Yuanfang Xie; Jiao Lan; Jifei Miao (Acta Neuropathologica Communications)
Abstract TAR DNA-binding protein 43 (TDP-43) has emerged as a critical player in neurodegenerative disorders, with its dysfunction implicated in a wide spectrum of diseases including amyotrophic lateral sclerosis (ALS), frontotemporal lobar degeneration (FTLD), and Alzheimer’s disease (AD). This comprehensive review explores the multifaceted roles of TDP-43 in both physiological and pathological contexts. We delve into TDP-43’s crucial functions in RNA metabolism, including splicing regulation, mRNA stability, and miRNA biogenesis. Particular emphasis is placed on recent discoveries regarding TDP-43’s involvement in DNA interactions and chromatin dynamics, highlighting its broader impact on gene expression and genome stability. The review also examines the complex pathogenesis of TDP-43-related disorders, discussing the protein’s propensity for aggregation, its effects on mitochondrial function, and its non-cell autonomous impacts on glial cells. We provide an in-depth analysis of TDP-43 pathology across various neurodegenerative conditions, from well-established associations in ALS and FTLD to emerging roles in diseases such as Huntington’s disease and Niemann-Pick C disease. The potential of TDP-43 as a therapeutic target is explored, with a focus on recent developments in targeting cryptic exon inclusion and other TDP-43-mediated processes. This review synthesizes current knowledge on TDP-43 biology and pathology, offering insights into the protein’s central role in neurodegeneration and highlighting promising avenues for future research and therapeutic interventions.